Contemporary Perspectives on Financial Governance and Performance in Indonesia’s Diverse Institutions - Pratama, Aditya Rizky; Priskila, Aliya; Simanjuntak, Andi Immanuel; Tan, Andreas; Hartanto, Andrew; Clarissa, Anastasia; Aprillia, Ayu Triana Andra; Andika, David; Priambodo, Dedy; Christabel, Felicia; Sari, Fransiska Widya; Yuwono, Giovanni P.; Yunita, Ivana; Suryanto, Kenny; William, Kenny; Widjaja, Kresensia Claudia; Prayoga, Krisna Yuda; Sin, Liem Gai; Purnomo, Purnomo; Wahyuni, Reni; Andika, Rony; Samsi, Samsi; Angeline, Sheren; Nathania, Sherlyne; Karolus, Silvester; Darma, Teddy Surya; Lestari, Vania; Alexander, Vincent; Melani, Vina; Sugiharto, Victor; Jonathan, William; Satria, Yohanes (AIBPM Publisher, 2026)
Contemporary Perspectives on Financial Governance and Performance in Indonesia’s Diverse Institutions provides a timely and insightful exploration of the evolving financial landscape within Indonesia’s multifaceted institutional framework. The chapters presented in this book reflect not only academic rigor but also a strong relevance to practical challenges faced by organizations today.This compilation brings together research-driven perspectives and empirical insights that are vital for understanding how governance mechanisms influence financial performance across various sectors. By bridging theoretical foundations with real-world applications, this book offers valuable knowledge for scholars, practitioners, and decision-makers alike.As an expert in the field, I find this work a significant contribution to the discourse on financial governance in emerging economies and a commendable effort in fostering collaboration across disciplines and institutions.